Traumatic rib fractures: a marker of severe injury. A nationwide study using the National Trauma Data Bank - Jesse Peek; Yassine Ochen; Noelle Saillant; Rolf H. H. Groenwold; Luke P. H. Leenen; Tarsicio Uribe‐Leitz; Roderick M. Houwert; Marilyn Heng (2020)
Background In recent years, there has been increasing interest in the treatment of patients with rib fractures. However, the current literature on the epidemiology and outcomes of rib fractures is outdated and inconsistent. Furthermore, although it has been suggested that there is a large heterogeneity among patients with traumatic rib fractures, there is insufficient literature reporting on the outcomes of different subgroups. Methods A retrospective cohort study using the National Trauma Data Bank was performed. All adult patients with one or more traumatic rib fractures or flail chest who were admitted to a hospital between January 2010 and December 2016 were identified by the International Classification of Diseases Ninth Revision diagnostic codes. Results Of the 564 798 included patients with one or more rib fractures, 44.9% (n=2 53 564) were patients with polytrauma. Two per cent had open rib fractures (n=11 433, 2.0%) and flail chest was found in 4% (n=23 388, 4.1%) of all cases. Motor vehicle accidents (n=237 995, 51.6%) were the most common cause of rib fractures in patients with polytrauma and flail chest. Blunt chest injury accounted for 95.5% (n=5 39 422) of rib fractures. Rib fractures in elderly patients were predominantly caused by high and low energy falls (n=67 675, 51.9%). Ultimately, 49.5% (n=2 79 615) of all patients were admitted to an intensive care unit, of whom a quarter (n=146 191, 25.9%) required invasive mechanical ventilatory support. The overall mortality rate was 5.6% (n=31 524). Discussion Traumatic rib fractures are a marker of severe injury as approximately half of patients were patients with polytrauma. Furthermore, patients with rib fractures are a very heterogeneous group with a considerable difference in epidemiology, injury characteristics and in-hospital outcomes. Worse outcomes were predominantly observed among patients with polytrauma and flail chest. Future studies should recognize these differences and treatment should be evaluated accordingly. Level of evidence II/III.